2002
DOI: 10.2118/76812-pa
|View full text |Cite
|
Sign up to set email alerts
|

Perforating for Stimulation: An Engineered Solution

Abstract: Summary Point-source perforating has reduced fracture-stimulation expenses in the south Texas Lobo trend. Although the producing intervals frequently exceed 100 ft, the operator typically perforates the bottom 5 ft of the interval. Data collected during perforating are used to design optimized fracture-stimulation treatments. The optimized treatments average 55% less proppant than the jobs designed previously with conventional practices that had perforations across the entire pay interval. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Similar behavior was described by Lestz [1]. In a Wilcox zone in a different area (as seen in the log sections in Figure 9) wells were typically perforated as seen for Well A -with several lobes of sand perforated and then a large (on the order of 500,000 lb of 16-30 RC sand) fracture treatment pumped.…”
Section: Case History Nosupporting
confidence: 69%
“…Similar behavior was described by Lestz [1]. In a Wilcox zone in a different area (as seen in the log sections in Figure 9) wells were typically perforated as seen for Well A -with several lobes of sand perforated and then a large (on the order of 500,000 lb of 16-30 RC sand) fracture treatment pumped.…”
Section: Case History Nosupporting
confidence: 69%
“…Perforating a small interval minimizes the creation of multiple fractures and SO events. Lestz et al [35] give more details.…”
Section: Design Modification Proceduresmentioning
confidence: 99%
“…Only more recent studies have shown that perforating for hydraulic fracturing is not the same as perforating for production. 10,[12][13][14][15] The following paragraphs provide a quick overview of the most important criteria for perforating for hydraulic fracturing.…”
Section: Spe 90238mentioning
confidence: 99%
“…The limited-entry perforation technique became popular and was used to keep the number of perforations to a reasonable limit. 2,13 The idea was that the limited number of perforations would create excess perforation-friction pressure, which, in theory, would increase the bottomhole treating pressure to larger than the pressure necessary to break down higher-stress zones, thus distributing the fracturing treatment to all perforated layers. This technique was successful in some areas.…”
Section: Perforated Intervalmentioning
confidence: 99%